2010
DOI: 10.1093/jac/dkq186
|View full text |Cite
|
Sign up to set email alerts
|

Piperine as an inhibitor of Rv1258c, a putative multidrug efflux pump of Mycobacterium tuberculosis

Abstract: The results of this study are suggestive of piperine's involvement in the inhibition of clinically overexpressed mycobacterial putative efflux protein (Rv1258c). Piperine may be useful in augmenting the antimycobacterial activity of rifampicin in a clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(106 citation statements)
references
References 28 publications
5
101
0
Order By: Relevance
“…There are several reports in the literature where natural products have demonstrated enhancement of antimicrobial activity (Khan et al, 2006;Stavri et al, 2007;Werle, 2008;Kumar et al, 2008;Lechner et al, 2008;Sharma et al, 2010). However, the number of natural compounds behaving synergistically with antifungals is minimal.…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports in the literature where natural products have demonstrated enhancement of antimicrobial activity (Khan et al, 2006;Stavri et al, 2007;Werle, 2008;Kumar et al, 2008;Lechner et al, 2008;Sharma et al, 2010). However, the number of natural compounds behaving synergistically with antifungals is minimal.…”
Section: Introductionmentioning
confidence: 99%
“…Among eleven piperic acid ester derivatives, 2-(3,4-dihydroxyphenyl)ethyl ester [4] showed the highest cytotoxicity against OSCC cell lines (mean CC 50 =17 μM), followed by (4-methoxyphenyl)methyl ester (38 μM) [1], 2-(4-methoxyphenyl)ethyl ester [5] (42 μM), 2-(4-hydroxyphenyl)ethyl ester (46 μM) [3], 2-phenylethyl ester [7] (61 μM) and 2-(3,4-dimethoxyphenyl)ethyl ester [6] (102 μM). On the other hand, (4-hydroxy-3-methoxyphenyl)methyl ester [2] (>368 μM), 3-phenylpropyl ester [8], 4-phenyl-2-butyl ester [9], 4-phenylbutyl ester [10] and decyl ester [11] (>400 μM) were essentially inactive (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…When four OSCC cell lines and three normal oral cells were used, [1] showed the highest TS value (>10.5), followed by [4] (8.0), [7] (>6.6), [3] (2.6), [6] (1.9), [5] Table I). [4] showed the highest PSE value (47.0), followed by [1] (>27.8), [7] (>10.8), [3] (5.7), [5] Table I). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…; such as its role in inhibition of Rv1258c, a putative multidrug efflux pump of M. tuberculosis. 46 The piperine we obtained from the endophytic Periconia sp. was naturally functional and the spectroscopic study of this compound revealed 99% similarity with piperine from the host itself.…”
Section: Resultsmentioning
confidence: 99%